1995
DOI: 10.1152/ajprenal.1995.268.5.f953
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitric oxide on renin secretion. II. Studies in the perfused juxtaglomerular apparatus

Abstract: To examine the possible role of NO in macula densa control of renin secretion, we examined the effects of varying NO availability on renin release in the isolated perfused rabbit juxtaglomerular apparatus (JGA). Gradual increments of luminal Na/Cl concentration ratio (mM/mM) from 26/7 over 46/27, 66/47, to 86/67 caused a progressive decrease in renin secretion from (as log of nano-Goldblatt hog units vs. time, i.e., log nGU/min) 1.09 +/- 0.34 to 0.46 +/- 0.24 log nGU/min, with the greatest change occurring at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 0 publications
0
36
0
Order By: Relevance
“…Some ongoing studies focus on the potential role of cGK II in regulation of renin release. However, in general cGMP regulation of renin release seems to be complex and currently not well understood since studies using different cGMP-elevating agents (ANP, NO, and sodium nitroprusside [SNP]), or different cell or tissue systems (isolated perfused rat kidneys, renal cortex slices or cells, isolated JG cells or JG apparatus), have concluded that cGMP can have stimulatory, inhibitory, or biphasic effects on renin release (10,(29)(30)(31)(32). This may imply that there are cGMP-independent effects of some agonists and that there are different cGMP targets of action or different complexities of regulatory feedback systems present in the various cell/tissue preparations.…”
Section: Discussionmentioning
confidence: 99%
“…Some ongoing studies focus on the potential role of cGK II in regulation of renin release. However, in general cGMP regulation of renin release seems to be complex and currently not well understood since studies using different cGMP-elevating agents (ANP, NO, and sodium nitroprusside [SNP]), or different cell or tissue systems (isolated perfused rat kidneys, renal cortex slices or cells, isolated JG cells or JG apparatus), have concluded that cGMP can have stimulatory, inhibitory, or biphasic effects on renin release (10,(29)(30)(31)(32). This may imply that there are cGMP-independent effects of some agonists and that there are different cGMP targets of action or different complexities of regulatory feedback systems present in the various cell/tissue preparations.…”
Section: Discussionmentioning
confidence: 99%
“…As reviewed recently by Liang and Knox (50) and by Ortiz and Garvin (80), there is evidence that NO reduces sodium reabsorption in all tubular segments, including the proximal tubule (50,80), thick ascending limb (78,79), distal tubules, and cortical collecting ducts (80), although medullary nephron segments and collecting ducts remain to be studied in detail. Studies have also demonstrated that tubuloglomerular feedback control of afferent arteriolar resistance is influenced by macula densa NO production, thereby enhancing autoregulation of renal blood flow, GFR, and renin secretion (30,37,53,75,122,128).…”
Section: No Production and The Overall Regulation Of Renal Functionmentioning
confidence: 99%
“…Many investigators have reported that NO stimulates renin secretion, both in vivo (21,25,29) and in the perfused kidney (15,16), while early work reported an inhibitory NO effect on renin secretion (39). Some authors suggest that NO from the macula densa cells may stimulate renin release, while NO derived from the endothelial cells in the afferent arteriole may inhibit renin secretion (2,4,12). Current concepts are seemingly rather complex (30).…”
mentioning
confidence: 99%